A direct simple shear device to study static liquefaction triggering under constant shear drained loading. Issue 2 (6th April 2019) - Reid, D.; Fourie, A.
Abstract : The development of a direct simple shear device to carry out constant shear drained (CSD) tests is outlined. The purpose of the device is to study static liquefaction instability triggered by a rising phreatic surface under principal stress directions representative of conditions below a slope. A series of tests on a laboratory-standard sand are outlined, indicating (a) brittle instability under a drained increasing phreatic surface, (b) a reasonable trend between instability stress conditions and sample density, and (c) general agreement between the qualitative behaviour seen in the new device and previous CSD testing carried out on saturated samples under dead weight. The sensitivity of instability stress conditions to sample density is emphasised.